2020
DOI: 10.1186/s13054-020-02976-6
|View full text |Cite
|
Sign up to set email alerts
|

Significance of body temperature in elderly patients with sepsis

Abstract: Background Elderly patients have a blunted host response, which may influence vital signs and clinical outcomes of sepsis. This study was aimed to investigate whether the associations between the vital signs and mortality are different in elderly and non-elderly patients with sepsis. Methods This was a retrospective observational study. A Japanese multicenter sepsis cohort (FORECAST, n = 1148) was used for the discovery analyses. Significant discovery results were tested for replication using two validation … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
40
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 53 publications
(41 citation statements)
references
References 42 publications
1
40
0
Order By: Relevance
“…In a recent study, Shimazui et al [1] reported that body temperature (BT) on ICU admission exhibited different predictive values in elderly and non-elderly patients with sepsis, and only hypothermia (BT < 36.0°C) was associated with increased mortality in non-elderly patients while hyperthermia (BT > 38.3°C) was not. A few issues should be noted.…”
Section: And Shiping Zhu 2*mentioning
confidence: 99%
“…In a recent study, Shimazui et al [1] reported that body temperature (BT) on ICU admission exhibited different predictive values in elderly and non-elderly patients with sepsis, and only hypothermia (BT < 36.0°C) was associated with increased mortality in non-elderly patients while hyperthermia (BT > 38.3°C) was not. A few issues should be noted.…”
Section: And Shiping Zhu 2*mentioning
confidence: 99%
“…We read with great interest the recent article by Shimazui et al who concluded that in septic patients, mortality in non-elderly patients was increased with hypothermia and decreased with fever, while mortality in elderly patients was not associated with body temperature (BT) [1]. We would like to make some comments.…”
mentioning
confidence: 97%
“…We would like to make some comments. As was alluded to by the authors themselves, BT measurement can be potentially confounded by various factors, including variation in the site of temperature measurement and whether or not patients receive antipyretics or targeted temperature management [1]. Nearly half of critically ill patients, especially those with septic shock, have or develop acute kidney injury (AKI) and 20-25% need renal replacement therapy (RRT) within the first week of their stay [2].…”
mentioning
confidence: 99%
See 2 more Smart Citations